Modeling of the Terrain features of Zliten water basins (Kaam-mager) using GIS - et. al., Abd Rahman Issa Al-Ghafoud, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Modern technologies have provided great possibilities in studies of the surface of the earth, especially the study of water basins in terms of analyzing the characteristics of those basins in terms of slopes, heights, levels, and others. The research dealt with the detection and analysis of the topographic characteristics of the basins of the Gamaam Majer valley within the administrative boundaries of the Zliten region. The research concluded a number of conclusions, the most prominent of which is the preference of GIS in geomorphological studies, as it provides the easiest and easiest ways to deal with maps.